Workshop on Data Analysis using Python at JNE - Bakti Siregar; Clara Della Evania; Yosia (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital transformation has been applied to all areas of a business, fundamentally changing how a company identifies and solves problems it is depending on data analysis. However, the demand for data analysts is growing fast, yet recruiters are struggling to find them. Therefore, the Department of Statistics at Matana University felt that it was necessary to carry out a workshop on data analysis. In this case, the writer has implemented a Pengabdian Kepada Masyarakat (PKM) at JNE. The purpose of this workshop is to provide benefits to our partner company (JNE) regarding data analysis. There were twenty participants in this activity, and it was conducted using the practicum method. The instructor also involves at least two students as assistants in each session. The implication of the training is that it changes the data analysis skills of the participants, even ordinary people. Soon, the Learning Center team of JNE with Matana University will move to more advanced topics.